2003
DOI: 10.1007/s00066-003-1022-3
|View full text |Cite
|
Sign up to set email alerts
|

Induratio penis plastica

Abstract: In our experience radiotherapy is not suitable for all stages of IPP. Only patients in the early stages of IPP-especially the ones who suffer from painful erection-should be considered suitable for treatment with ionising radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“… 4 When comparing the results of our patient collective with corresponding studies, similar results were observed in symptom improvement and pain relief after irradiation ( Table 3 ). 12 , 14 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“… 4 When comparing the results of our patient collective with corresponding studies, similar results were observed in symptom improvement and pain relief after irradiation ( Table 3 ). 12 , 14 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…High-energy electron beams, either alone or combined with high-energy photon beams, are widely used in radiation therapy [7,11,18,28,34,35]. In many clinical situations, such as in the treatment of head-and-neck tumors or breast cancer, photon and electron beams are directly abutted [29,30].…”
Section: Introductionmentioning
confidence: 99%